Exposure‐based therapy changes amygdala and hippocampus resting‐state functional connectivity in patients with posttraumatic stress disorder. Issue 10 (10th September 2018) - Zhu, Xi; Suarez‐Jimenez, Benjamin; Lazarov, Amit; Helpman, Liat; Papini, Santiago; Lowell, Ari; Durosky, Ariel; Lindquist, Martin A.; Markowitz, John C.; Schneier, Franklin; Wager, Tor D.; Neria, Yuval
Abstract : Background: Recent research suggests that posttraumatic stress disorder (PTSD) is associated with altered amygdala and hippocampal resting‐state functional connectivity (rsFC). However, less research has examined whether Prolonged Exposure (PE), a first line exposure‐based treatment for PTSD, has the potential to alter resting state neural networks. Methods: A total of 24 patients with PTSD and 26 matched trauma‐exposed healthy controls (TEHCs) underwent resting‐state functional magnetic resonance imaging (fMRI) at baseline. PTSD patients were scanned a second time after completing 10‐session PE in which patients narrated a detailed trauma account (imaginal exposure) and confronted trauma reminders (in vivo exposure) to extinguish trauma‐related fear responses. TEHC were scanned again following a 10‐week waiting period. Seed regions of interest (ROIs) included centromedial amygdala (CMA), basolateral amygdala (BLA), and the hippocampus. Results: Post‐ versus pretreatment comparisons indicated increased rsFC of the BLA and CMA with the orbitofrontal cortex (OFC), and hippocampus‐medial prefrontal cortex (mPFC) among patients with PTSD, but not among TEHC participants. Conclusions: Enhanced amygdala and hippocampus rsFC with prefrontal cortical regions following PE could underlie improved capacity for inhibition and re‐evaluation of threat, and heightened memory encoding and retrieval ability, respectively. These findings encourage further investigation of this circuitry as a therapeutic target in PTSD.